Two new species and four unknown larvae of Amphinemurinae (Plecoptera, Nemouridae) from southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai; Murányi, Dávid (Zootaxa, 2021)
Two new nemourid species, Amphinemura meizhouensis sp. n. and A. tulipa sp. n., are described from Guangdong Province and Guangxi Zhuang Autonomous Region, respectively. Four larvae of the stonefly subfamily Amphinemurinae, A. bifascia Mo, Wang, Yang & Li, 2020, A. hamiornata Li & Yang, 2008, A. yao Mo, Yang, Wang & Li, 2017, and Indonemoura scalprata (Li & Yang, 2007) are described and illustrated on the basis of recently collected specimens from southern China. The female adult of A. hamiornata is also described from the type locality. Both new species are typical members of the A. sinensis (Wu, 1926) species group and the taxonomic relationships are discussed with related congeners.